Individual demand for local public schooling: Evidence from Swedish survey data - Åsa Ahlin; Eva Johansson (Institute for Labour Market Policy Evaluation (IFAU), 2001)
In this paper we investigate the demand for local public school expenditures in Sweden using survey data, a method previously never applied to Swedish data. We compare our results to those of earlier US studies, where the same method is used in a different institutional setup. Estimating a linear demand specifica-tion, we find that demand is inelastic with respect to income and taxprice, much in line with previous Swedish findings in a median voter framework. Es-timation of a log-linear demand specification indicates that the elasticities of demand for schooling are higher in Sweden than in the US. Testing the hy-pothesis that municipal employees tend to have a higher demand for public spending than others, we conclude that income, as well as taxprice and grants, enters the demand function differently for the two groups of employees.
Keywords: C25; H40; H72; 330; individual demand; local public schooling; survey data; public employees